Dipturus leptocaudus, Thintail Skate - Pollom, R. (2020)
The Thintail Skate (Dipturus leptocaudus) is a medium-sized (to 88 cm total length) skate that occurs in the Southwest Atlantic from Santa Catarina, Brazil to Uruguay (and possibly Argentina). It inhabits the continental shelf and upper slope at depths of 10–550 m. It is captured in commercial deep-water trawl, longline, and gillnet fisheries, which operate throughout its known range. Little information is available regarding the amount of catches due to identification issues. Dipturus spp. were the most abundant elasmobranchs caught in the monkfish (Lophius gastrophysus) deep-water gillnet fishery off southern Brazil, which intensified in the 2000s. These industrial gillnet fisheries often also target skates, and have led to declines in other ecologically similar species such as angel sharks (Squatina spp.). Dipturus spp. were shown to be highly vulnerable to such fisheries in a productivity-susceptibility analysis. There are also deep-water trawlers operating in the area targeting shrimp and squid, which are intense. Overall, due to the presence of intense and inadequately managed trawl fisheries that operate throughout its range, it is suspected that the Thintail Skate has undergone a population reduction of 30–49% over the past three generations (21 years), and it is assessed as Vulnerable A2d.